STUDI LITERATUR: KEMAMPUAN PENALARAN MATEMATIS SISWA DALAM MENYELESAIKAN SOAL BERBASIS MASALAH - Karila Rezki Afinadhita; Agung Prasetyo Abadi (IKIP Siliwangi, 2022)
This article aims to examine students' mathematical reasoning abilities in finishing items based problems. The researcher reviewed several literatures related to mathematical reasoning ability, where the method used was literature study. The results of studies that have been carried out by researchers are problem-based questions that have an important role in mathematical reasoning abilities. Through mathematical reasoning abilities students can think logically, critically, effectively, and efficiently. This thinking equips students to be able to finishing items based problems. Next, based on a study of some literature, there are several indicators of mathematical reasoning ability that must be achieved to categorize high, medium, and low mathematical reasoning abilities in finishing items based problems. In this case, the researcher seeks support from experts to strengthen the argument during the study process.